Peran Lembaga Penegak Hukum Dalam Proses Perampasan Aset - Arianto, Andhie Fajar (JURNAL USM LAW REVIEW, 2024)
The purpose of this study is to the strategic role of law enforcement agencies in the asset confiscation process in Indonesia, by highlighting the challenges faced, such as overlapping regulations, lack of coordination between agencies, and technical obstacles in tracing and confiscating assets across countries. Overlapping regulations make the asset confiscation process longer. This provides an opportunity for corruptors to hide or transfer their assets. The role of law enforcement agencies in Indonesia, including the police, prosecutors, and courts, greatly determines the success of the asset confiscation process and the recovery of state losses. This research method uses a normative legal approach. The results of this study Law enforcement officers must be involved in tight collaboration at the national, bilateral, and multilateral levels. To carry out the asset recovery process, a central team and task force with special expertise are needed, which serve as the main driving force behind the investigation and prosecution of asset recovery efforts. The use of information technology can help in tracking assets from corruption hidden abroad or in the form of crypto assets. Improving Indonesia's asset confiscation system requires a comprehensive approach that includes harmonization of regulations with the ratification of the Asset Confiscation Bill, strengthening coordination between law enforcement agencies, and utilizing information technology. Thus, efforts to repair state losses caused by criminal acts of corruption can be carried out better. Tujuan dari penelitian ini peran strategis lembaga penegak hukum dalam proses perampasan aset di Indonesia, dengan menyoroti tantangan yang dihadapi, seperti tumpang tindih regulasi, minimnya koordinasi antar lembaga, serta kendala teknis dalam penelusuran dan penyitaan aset lintas negara. Tumpang tindih regulasi menyebabkan proses perampasan aset menjadi lebih panjang. Hal ini memberikan kesempatan bagi pelaku korupsi untuk menyembunyikan atau mengalihkan asetnya. Peran lembaga penegak hukum di Indonesia, termasuk kepolisian, kejaksaan, dan pengadilan, sangat menentukan keberhasilan proses perampasan aset dan pemulihan kerugian negara. metode penelitian ini menggunakan pendekatan yuridis normatif. Hasil penelitian ini Aparat penegak hukum harus terlibat dalam kolaborasi yang ketat di tingkat nasional, bilateral, dan multilateral. Untuk melaksanakan proses pemulihan aset, diperlukan tim dan gugus tugas pusat dengan keahlian khusus, yang berfungsi sebagai kekuatan pendorong utama di balik investigasi dan penuntutan upaya pemulihan aset. Penggunaan teknologi informasi dapat membantu dalam melacak aset hasil korupsi yang disembunyikan di luar negeri atau dalam bentuk aset kripto. Perbaikan sistem perampasan aset Indonesia memerlukan pendekatan yang komprehensif yang mencakup harmonisasi regulasi dengan pengesaha RUU Perampasan Aset, penguatan koordinasi antar lembaga penegak hukum, dan pemanfaatan teknologi informasi. Dengan demikian, upaya untuk memperbaiki kerugian negara yang disebabkan oleh tindak pidana korupsi dapat dilakukan dengan lebih baik.